2022
DOI: 10.1038/s41467-022-31667-9
|View full text |Cite
|
Sign up to set email alerts
|

Widespread increasing vegetation sensitivity to soil moisture

Abstract: Global vegetation and associated ecosystem services critically depend on soil moisture availability which has decreased in many regions during the last three decades. While spatial patterns of vegetation sensitivity to global soil water have been recently investigated, long-term changes in vegetation sensitivity to soil water availability are still unclear. Here we assess global vegetation sensitivity to soil moisture during 1982-2017 by applying explainable machine learning with observation-based leaf area in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 70 publications
5
57
1
Order By: Relevance
“…Grasslands indicate high S ppt , and their S ppt is still increasing in the past two decades (Table 2). This result is consistent with the elevated soil moisture sensitivity found by Li et al (2022) in the arid regions around the globe. This implies that climate change would introduce greater instability of vegetation productivity and carbon sink in grassland ecosystems, making them be more vulnerable.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Grasslands indicate high S ppt , and their S ppt is still increasing in the past two decades (Table 2). This result is consistent with the elevated soil moisture sensitivity found by Li et al (2022) in the arid regions around the globe. This implies that climate change would introduce greater instability of vegetation productivity and carbon sink in grassland ecosystems, making them be more vulnerable.…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that S ppt varied greatly across the globe, with high S ppt values in arid regions and low S ppt in mesic regions (Figure 1). This result is consistent with prior ground observations, which illustrate higher S ppt in more arid ecosystems (Huxman et al, 2004; Knapp et al, 2015), and is also consistent with a reported spatial pattern of global soil moisture sensitivity (Li et al, 2022). For example, a meta‐analysis by Liu et al (2021) for global grasslands suggests that ANPP has higher sensitivity to precipitation treatments at dry sites than at nonwater‐limited sites.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study suggests that low soil moisture is the dominant driver of dryness stress on vegetation, which weakens the capacity for carbon uptake in ecosystems (Liu et al, 2020). Furthermore, the sensitivity of vegetation to soil moisture has substantially increased since 1982 (Li, Migliavacca, et al, 2022). Previous studies found that not only temperature, but also plant‐available water affect autumn phenological processes (Fu et al, 2022; Luo et al, 2021; Tao et al, 2021; Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Under the continuous impact of climate change, the spatial distribution of climate and land cover classifications is assumed to be changed in the coming century (Beck et al 2018). It is also predicted that drying trend will continuously dominate and amplify climate change impact (Deng et al 2020, Li et al 2022. The pattern of the SM-LAI interaction in different regions is expected to change due to the shift in climate and land cover types.…”
Section: Discussionmentioning
confidence: 99%